TMT-Based Quantitative Proteomic Analysis Reveals the Response of Tomato (Solanum lycopersicum L.) Seedlings to Ebb-and-Flow Subirrigation - Kelei Wang; Muhammad Moaaz Ali; Tianxin Guo; Shiwen Su; Xianzhi Chen; Jian Xu; Faxing Chen (Agronomy, 2022)
Ebb-and-flow subirrigation (EFI) is a water-saving and environmentally friendly irrigation method that can effectively improve water use efficiency and promote plant growth. In this study, we elucidated the effects of ebb-and-flow subirrigation on the protein levels in tomato roots in comparison with top sprinkle irrigation (TSI) and used an integrated approach involving tandem mass tag (TMT) labeling, high-performance liquid chromatography (HPLC) fractionation, and mass-spectrometry (MS)-based analysis. A total of 8510 quantifiable proteins and 513 differentially accumulated proteins (DAPs) were identified, of which the expressions of 283 DAPs were up-regulated, and 230 DAPs were down-regulated in the EFI vs. TSI treatment comparison. According to proteomic data, we performed a systematic bioinformatics analysis of all the identified proteins and DAPs. The DAPs were most significantly associated with the terms ‘metabolic process’, ‘anchored component of membrane’, ‘oxidoreductase activity’, ‘phenylpropanoid biosynthesis’, and ‘biosynthesis of secondary metabolites’ according to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes enrichment (KEGG) analysis. The 272 DAPs were classified into 12 subcellular components according to their subcellular localization. Furthermore, the activities of SOD, POD, CAT, GR, and APX in tomato roots were remarkably increased under EFI, while the MDA content was decreased compared with TSI. Correlation analysis among activities of enzymes and their related DAPs showed that 30 DAPs might be responsible for the regulation of these enzymes. The results showed that ebb-and-flow subirrigation could induce a series of DAPs responses in tomato roots to be adapted to the new mode of water supply.